STRATEGI KOMUNIKASI “SEMARANG WEGAH NYAMPAH” DALAM MEMBANGUN AWARENESS MASYARAKAT UNTUK MENGURANGI SAMPAH PLASTIK - Wulan Asih Setyarini (Jurnal Riptek, 2020)
A number of impacts on digital developments have actually created new problems. The rise of online shopping activities and food delivery has resulted in an increase in the amount of waste, especially plastik and packaging waste. This problem is getting worse due to the lack of public knowledge about waste management. Some of the waste was also found clogging the waterways which resulted in flooding at several area and clogging the flood pumps which made it malfunctioning. For this reason, the Semarang City Government issued a regulation to control the use of plastik which is expected to reduce the amount of waste generated in the city of Semarang. Without a good communication strategy, a program will not be succeed. Conducting to succeed the program and spread off the regulation, a package of communication strategy called Semarang Wegah Nyampah was completely set and prepared. This series of communication programs aims to build public awareness to care more about the environment in the city of Semarang, which includes waste management and reduction the use of plastik in daily activities. After analyzing the situation and identifying the target audience, key messages are then determined to be conveyed through various media and digital channels for campaign effectiveness. This campaign resulted good engagement with the target audience. The communication activities raises an existence of public awareness that create various actions related to waste management.